Building on Entrepreneurial Team Theory: A Women Context - Ndinguri, Erastus; Hill, Jessica (Archives of Business Research, 2023)
Using literature on entrepreneurial teams, we examine ways in which technology can be used as a connecting link to build women entrepreneurial teams. The study theorizes that use of technology creates a new realm (structural uncertainty) that gives rise to entrepreneurial women networks and women entrepreneurial opportunities (common interests) which in turn creates strong interdependence that provides a suitable environment for women entrepreneurial teams. We conceptualize that women use of technology for networking and mentoring purposes can be a first step in building the teams.